IMPLEMENTASI DIGITAL MARKETING DAN PENGOPERASIAN WEBSITE BERBASIS AISAS WISATA AGRAPANA DALAM MEWUJUDKAN SDG'S DESA SUMBER KALONG, KABUPATEN BONDOWOSO - Marmono Singgih; Intan Nurul Awwaliyah; Sumani Sumani; Arnis Budi Susanto; Ema Desia Prajitiasari; Andriana Andriana; Jadwa Jaifar Hidayahtullah Giri Syahputra Syahputra; Sherina Naylil Amani; Dika Wijaya Kusuma Purwadi; Fifin Nur Aida (LPPM Universitas Andalas, 2025)
The collaboration program at Agrapana Tourism, Sumber Kalong Village, Bondowoso Regency, focuses on enhancing the competitiveness and sustainability of the destination through digital marketing optimization and website management. The objective of this program is to increase the number of visitors and revenue for Agrapana Tourism by strengthening digital marketing strategies and developing a more efficient financial system. The methods used involve a community-based approach, beginning with an initial survey to understand the needs and conditions of the partners, followed by a Focus Group Discussion (FGD) to formulate the right strategies, and then intensive training and mentoring in digital marketing and financial management. The AISAS model (Attention, Interest, Search, Action, Share) is applied to increase Agrapana’s digital visibility across various online platforms. Additionally, the program includes the provision of support tools, such as an Android-based cash register and a website, as well as mentoring on their use. The results of the program show a significant improvement in the tourism managers' skills in managing digital content, maximizing SEO strategies, and enhancing the efficiency of the financial system through the use of digital cash registers. This program not only successfully strengthens the capacity of the local community to manage and develop tourism potential independently but also opens opportunities for sustainable economic growth and boosts Agrapana's reputation as a leading local tourist destination. This success is expected to serve as a model for the development of other tourist villages in the Bondowoso area and beyond, thereby supporting broader local economic empowerment.